Goldsmiths from mompox: occupational health and work (2001)
The working and occupational health conditions of 37 goldsmiths and 14 workshops in the city of Mompox, Bolívar, were studied. An assessment instrument comprising four questionnaires was employed for identification of productive unit, identification of craftsman, assessment of health conditions and assessment of working conditions. The characterization of the working population, the working places present during the process and the social and working context of the goldsmiths were achieved. The results conform with the traditional characteristics of the informal sector in Colombia: precarious living conditions, minimum coverage of social security, low income, low technological complexity, taskwork, low training and low degree of school education.